2022
DOI: 10.1182/blood.2021012561
|View full text |Cite
|
Sign up to set email alerts
|

Donor plasmacytoid dendritic cells limit graft-versus-host disease through vasoactive intestinal polypeptide expression

Abstract: Vasoactive intestinal peptide (VIP), an anti-inflammatory neuropeptide with pleiotropic cardio-vascular effects, induces differentiation of hematopoietic stem cells into regulatory dendritic cells that limit graft-versus-host disease (GvHD) in allogeneic hematopoietic stem cell transplant (HSCT) recipients. We have previously shown that donor plasmacytoid dendritic cells (pDCs) in bone marrow (BM) donor grafts limit the pathogenesis of GvHD. In this current study we show that murine and human pDCs express VIP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The gene expression patterns of Flt3L‐induced human and mouse pDCs are strikingly similar 200 . Therefore, donor pDCs limited pathogenic T‐cell inflammation while also balancing GVHD and GVL activities 191 …”
Section: Gut‐associated Pdcs and Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…The gene expression patterns of Flt3L‐induced human and mouse pDCs are strikingly similar 200 . Therefore, donor pDCs limited pathogenic T‐cell inflammation while also balancing GVHD and GVL activities 191 …”
Section: Gut‐associated Pdcs and Diseasementioning
confidence: 91%
“…200 Therefore, donor pDCs limited pathogenic Tcell inflammation while also balancing GVHD and GVL activities. 191 The essential role of pDCs has been validated in both humans and mice. Although clinical data hints that the transfer of donor-type pDCs may be a cellular therapy for GVHD prevention, 194 there is still a rigid demand for optimizing tolerogenic pDCs production therapy in GVHD, particularly how to manufacture adequate amounts of pDCs.…”
Section: Role Of Pdcs In Intestinal Graftversus-host Disease (Gvhd)mentioning
confidence: 99%
“…More recent studies showed that VIP enhances M2 macrophage polarization and promotes macrophages with a less-inflammatory physiologic profile that promotes tissue repair (88-90). We recently noted that VIP produced by activated T cells limits their proliferation in vitro (91), and VIP produced by donor plasmacytoid dendritic cells (pDCs) limits Graft-versus-Host Disease (GVHD) in vivo (92). The emerging immunoregulatory role of VIP on innate and adaptive immune functions makes it a candidate immunotherapy target.…”
Section: Implications Of Emerging Peptidebased Antagonists In Act Vip...mentioning
confidence: 99%
“…Moreover, PPIA participates in the modulation of various biological processes, including apoptosis, inflammation, transcription and intracellular signaling 16 19 . Previous studies suggest that the extracellular fractions of PPIA are potent pro-inflammatory mediators and PPIA is associated with a variety of inflammatory diseases 20 . Recent studies indicate that PPIA also plays a pivotal role in the development of human cancers 16 , including colon cancer 21 , hepatocellular carcinoma (HCC) 22 , multiple myeloma 23 , lung adenocarcinoma 24 and GC 25 .…”
Section: Introductionmentioning
confidence: 99%